PENGEMBANGAN MEDIA PEMBELAJARAN APLIKASI CANVA PADA FASE A BAB 2 AYO BERMAIN TEKS NONFIKSI “HATI-HATI” DI KELAS 1 SD NEGERI PALEBON 01 - Nafla Kapila Sumarga; Mudzanatun; Choirul Huda (STKIP Subang, 2025)
The research was successfully conducted at Palebon 01 Semarang Public Elementary School that teachers experience time constraints in creating interactive, innovative, and interesting learning media, so that learning tends to use conventional methods that cause students to quickly feel bored. The type of research used is RnD with the ADDIE research model, with the aim of developing canva application learning media on phase A chapter 2 material let's play non-fiction text